Prostaglandin E2 Via Steroidogenic Factor-1 Coordinately Regulates Transcription of Steroidogenic Genes Necessary for Estrogen Synthesis in Endometriosis - Attar, Erkut; Tokunaga, Hideki; Imir, Gonca; Yilmaz, M. Bertan; Redwine, David; Putman, Michael; Bulun, Serdar E. (Endocrine Soc, 2009)
Context: Products of at least five specific steroidogenic genes, including steroidogenic acute regulatory protein (StAR), which facilitates the entry of cytosolic cholesterol into the mitochondrion, side chain cleavage P450 enzyme, 3 beta-hydroxysteroid-dehydrogenase-2, 17-hydroxylase/17-20-lyase, and aromatase, which catalyzes the final step, are necessary for the conversion of cholesterol to estrogen. Expression and biological activity of StAR and aromatase were previously demonstrated in endometriosis but not in normal endometrium. Prostaglandin E-2 (PGE(2)) induces aromatase expression via the transcriptional factor steroidogenic factor-1 (SF1) in endometriosis, which is opposed by chicken-ovalbumin upstream- transcription factor (COUP-TF) and Wilms' tumor-1 (WT1) in endometrium. Objective: The aim of the study was to demonstrate a complete steroidogenic pathway leading to estrogen biosynthesis in endometriotic cells and the transcriptional mechanisms that regulate basal and PGE(2)-stimulated estrogen production in endometriotic cells and endometrium. Results: Compared with normal endometrial tissues, mRNA levels of StAR, side chain cleavage P450, 3 beta-hydroxysteroid- dehydrogenase-2, 17-hydroxylase/17-20-lyase, aromatase, and SF1 were significantly higher in endometriotic tissues. PGE(2) induced the expression of all steroidogenic genes; production of progesterone, estrone, and estradiol; and StAR promoter activity in endometriotic cells. Overexpression of SF1 induced, whereas COUP-TFII or WT1 suppressed, StAR promoter activity. PGE(2) induced coordinate binding of SF1 to StAR and aromatase promoters but decreased COUP-TFII binding in endometriotic cells. COUP-TFII or WT1 binding to both promoters was significantly higher in endometrial compared with endometriotic cells. Conclusion: Endometriotic cells contain the full complement of steroidogenic genes for de novo synthesis of estradiol from cholesterol, which is stimulated by PGE(2) via enhanced binding of SF1 to promoters of StAR and aromatase genes in a synchronous fashion. (J Clin Endocrinol Metab 94: 623-631, 2009)
Keywords: Element Binding-Protein; Stromal Cells; Aromatase Expression; Adipose Fibroblasts; P450 Expression; Cytochrome B(5); Breast-Cancer; Receptor; Star; Promoters